Response of wildebeest (Connochaetes taurinus) movements to spatial variation in long term risks from a complete predator guild. (May 2019) - Dröge, Egil; Creel, Scott; Becker, Matthew; Christianson, David; M'Soka, Jassiel; Watson, Fred
Abstract: Many studies have shown that behavioral responses to the risk posed by predators can carry costs for prey by reducing fecundity or survival, with consequent effects on population dynamics. Responses to risk include increased vigilance and reduced foraging, movement to safe habitats, increases or decreases in group size, and changes in patterns of movement. While we know that prey can detect and respond to both long term (LT) and short term (ST) variation in risk, field studies have only recently begun to consider how these responses might differ. Here, we hypothesize that prey movement patterns should respond differently to cues of LT and ST variation in risk. Specifically, cues of elevated LT risk might lead to decreased movement to improve the assessment of ST risk, while elevated ST risk might favor increased movement to reduce the proximity or duration of risks that are already assessed to be acute. We further hypothesize that decreases in movement are likely to be a general response to LT risk, while responses to ST risk are likely to vary in a manner that depends on the type of predator. In Liuwa Plain National Park, we found that wildebeest movements responded to the local intensity of predator use (LT risk), after controlling for other seasonal, diurnal and bottom-up effects. Speed decreased considerably and turning angles increased considerably, combining to markedly decrease linear movements. In contrast, immediate encounters with predators (ST risk) typically provoked fast, linear flight, and this effect was stronger for encounters with coursing predators. The effect of long term risk was to cause wildebeest to move more slowly and less linearly, i.e. to slow down and turn around, as part of a suite of behavioral responses, which also includes increased vigilance, that promote cautious assessment of ST risks when in locations with high levels of LT risk. This result has broad implications of understanding the influence of predation risk on foraging patterns of ungulates as this relationship is much more complex than simple avoidance of areas of 'high risk'.